Intermolecular interactions in crystals : fundamentals of crystal engineering - Novoa, Juan J.; Novoa, Juan J. (Royal Society of Chemistry, 2018)
"The field of crystal engineering concerns the design and synthesis of molecular crystals with desired properties. This requires an in-depth understanding of the intermolecular interactions within crystal structures. This new book brings together the latest information and theories about intermolecular bonding, providing an introductory text for graduates. The book is divided into three parts. The first part covers the nature, physical meaning and methods for identification and analysis of intermolecular bonds. The second part ... describes representative examples of the most relevant types of intermolecular bonds currently known to occur in molecular crystals. The third part describes how cooperativity affects the properties of intermolecular bonds, how they can be identified in crystals and how the information on intermolecular interactions and bonds can be used to design new molecular crystals. Each chapter is written by specialists in the topic being covered. This comprehensive textbook will provide a valuable resource for all students and researchers in the field of crystallography, materials science and supramolecular chemistry"--